1997
DOI: 10.1093/emboj/16.7.1501
|View full text |Cite
|
Sign up to set email alerts
|

Substrate specificity of the DnaK chaperone determined by screening cellulose-bound peptide libraries

Abstract: (Flynn et al., 1991; Landry et al., 1992; Hsp70 chaperones assist protein folding by ATP- Blond-Elguindi et al., 1993;Gragerov et al., 1994). With dependent association with linear peptide segments of respect to the binding motif and its amino acid composition, a large variety of folding intermediates. The molecular they yielded results in conflict with each other (Flynn et al., basis for this ability to differentiate between native 1991; Blond-Elguindi et al., 1993;Gragerov et al., 1994) and non-native confor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

38
732
2
4

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 757 publications
(776 citation statements)
references
References 32 publications
38
732
2
4
Order By: Relevance
“…The all-R-helical protein apoMb is employed as a model substrate. Chaperone binding sites are reported to be less common in segments corresponding to helices in native proteins (10). We have, however, found that there are relatively strong binding sites for DnaK along the apoMb sequence.…”
contrasting
confidence: 53%
See 2 more Smart Citations
“…The all-R-helical protein apoMb is employed as a model substrate. Chaperone binding sites are reported to be less common in segments corresponding to helices in native proteins (10). We have, however, found that there are relatively strong binding sites for DnaK along the apoMb sequence.…”
contrasting
confidence: 53%
“…The nonpolar character of each amino acid was ranked according to different scales to explore whether the results depend on the choice of the scale and how the nonpolar amino acid nature correlates with chaperone binding affinity ( Figure 9). The binding motif for DnaK is expected to have a three to five residue hydrophobic core (10). Therefore, we assessed the nonpolar character of the five central residues of each peptide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The molecular chaperone DnaKJE binds to the hydrophobic nascent polypeptide15 with formation of the ribosome–nascent chain/DnaKJE complex, preventing aggregation of nascent polypeptides during cell‐free protein synthesis 16. Addition of DnaKJE resulted in increased solubility of all Cx43–FLAG fusion proteins synthesized in cell‐free synthesis, indicating that DnaKJE acted as a molecular chaperone for reconstitution of Cx43–FLAG to liposomes (Figure S6, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Hsp60 (GroEL) and Hsp70 (DnaK) represent two well studied members of this class of proteins. Both Hsp60 and Hsp70 interact with nascent polypeptide chains and promote their folding by interacting with hydrophobic surfaces on substrate proteins (Gomez-Puertas et al, 2004;Kurt et al, 2006;Rudiger et al, 1997;Weissman et al, 1995). Once substrates are bound, the chaperone undergoes subsequent rounds of ATP hydrolysis causing conformational changes within the chaperone (Young et al, 2004).…”
Section: Introductionmentioning
confidence: 99%